Expected value of artificial intelligence in gastrointestinal endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Messmann, Helmut; Bisschops, Raf; Antonelli, Giulio; Libânio, Diogo; Sinonquel, Pieter; Abdelrahim, Mohamed; Ahmad, Omer F.; Areia, Miguel; Bergman, Jacques J. G. H. M.; Bhandari, Pradeep; Boskoski, Ivo; Dekker, Evelien; Domagk, Dirk; Ebigbo, Alanna; Eelbode, Tom; Eliakim, Rami; Häfner, Michael; Haidry, Rehan J.; Jover, Rodrigo; Kaminski, Michal F.; Kuvaev, Roman; Mori, Yuichi; Palazzo, Maxime; Repici, Alessandro; Rondonotti, Emanuele; Rutter, Matthew D.; Saito, Yutaka; Sharma, Prateek; Spada, Cristiano; Spadaccini, Marco; Veitch, Andrew; Gralnek, Ian M.; Hassan, Cesare; Dinis-Ribeiro, Mario (Endoscopy, 2022)
This ESGE Position Statement defines the expected value of artificial intelligence (AI) for the diagnosis and management of gastrointestinal neoplasia within the framework of the performance measures already defined by ESGE. This is based on the clinical relevance of the expected task and the preliminary evidence regarding artificial intelligence in artificial or clinical settings.Main recommendations: (1) For acceptance of AI in assessment of completeness of upper GI endoscopy, the adequate level of mucosal inspection with AI should be comparable to that assessed by experienced endoscopists. (2) For acceptance of AI in assessment of completeness of upper GI endoscopy, automated recognition and photodocumentation of relevant anatomical landmarks should be obtained in ≥90% of the procedures. (3) For acceptance of AI in the detection of Barrett’s high grade intraepithelial neoplasia or cancer, the AI-assisted detection rate for suspicious lesions for targeted biopsies should be comparable to that of experienced endoscopists with or without advanced imaging techniques. (4) For acceptance of AI in the management of Barrett’s neoplasia, AI-assisted selection of lesions amenable to endoscopic resection should be comparable to that of experienced endoscopists. (5) For acceptance of AI in the diagnosis of gastric precancerous conditions, AI-assisted diagnosis of atrophy and intestinal metaplasia should be comparable to that provided by the established biopsy protocol, including the estimation of extent, and consequent allocation to the correct endoscopic surveillance interval. (6) For acceptance of artificial intelligence for automated lesion detection in small-bowel capsule endoscopy (SBCE), the performance of AI-assisted reading should be comparable to that of experienced endoscopists for lesion detection, without increasing but possibly reducing the reading time of the operator. (7) For acceptance of AI in the detection of colorectal polyps, the AI-assisted adenoma detection rate should be comparable to that of experienced endoscopists. (8) For acceptance of AI optical diagnosis (computer-aided diagnosis [CADx]) of diminutive polyps (≤5 mm), AI-assisted characterization should match performance standards for implementing resect-and-discard and diagnose-and-leave strategies. (9) For acceptance of AI in the management of polyps ≥ 6 mm, AI-assisted characterization should be comparable to that of experienced endoscopists in selecting lesions amenable to endoscopic resection.